Problems of medical distance education of english-speaking students in a COVID-19 pandemic - Krut, O. S.; Krut, Yu. Ya.; Bohomolova, O. A.; Amro, I. G.; Круть, Олександра Степанівна; Круть, Юрій Якович; Богомолова, Оксана Андріївна; Амро, Ірина Геннадіївна (Запорізький державний медичний університет, 2021)
This article highlights both the positive and negative aspects of distance learning for students with English-language learning during the quarantine of the Сovid-19 pandemiс.
Keywords: distance learning; teacher; student; pandemic; modern technologies; modularity; relevance; flexibility; advantages; disadvantages; quarantine; coronavirus